THE INFLUENCE OF EDUCATIONAL BACKGROUND, FINANCIAL LITERACY, AND FINANCIAL PLANNING ON THE FINANCIAL BEHAVIOR OF MSME (CASE STUDY IN MSMES IN THE JAMBANGAN SUB-DISTRICT, SURABAYA CITY) - Lesmana, Arya Widi; Hidayat, Sjarief (International Journal of Economy, Education and Entrepreneurship (IJE3), 2023)
This study assessed how educational background, financial literacy, and financial planning impact the financial behaviour of MSMEs in the Jambangan Sub-District of Surabaya City. The study encompassed a total population of 969 MSMEs in this area. Quantitative research methods were employed, with data analysis conducted using Partial Least Squares. Data collection involved a questionnaire consisting of 17 questions. The sample criteria for this research were MSMEs engaged in financial planning and employing a minimum of 2 individuals, resulting in a sample size of 44 MSMEs in the Jambangan Sub-District of Surabaya City. The study's findings indicate that educational background, financial literacy, and financial planning positively and significantly influence the financial behaviour of MSMEs in the Jambangan Sub-District of Surabaya City